1986
DOI: 10.1016/0014-5793(86)81526-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the post‐translational processing of microvillar hydrolases is associated with a specific decreased expression of sucrase‐isomaltase and an increased turnover of glucose in Caco‐2 cells treated with monensin

Abstract: The biosynthesis and post‐translational processing of sucrase‐isomaltase and dipeptidylpeptidase IV were studied by L‐[35S]methionine labeling, immunoisolation with monoclonal antibodies and SDS‐PAGE in post‐confluent Caco‐2 cells treated with monensin (10 μM, 48 h). In addition to its classical effect on the post‐translational processing of both hydrolases, i.e. an inhibition of the conversion of the high‐mannose to the complex glycosylated form of the enzymes, monensin was found to have two other effects: a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…The enzyme had a molecular mass of approximately 115 kDa, and was found primarily associated with the cell-membrane fraction. These observations are in general agreement with those of other investigators who have used the Caco-2 cell line in their studies (Hauri et al, 1985;Rousset et al, 1986;Steiger et al, 1988;Matter et al, 1989).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The enzyme had a molecular mass of approximately 115 kDa, and was found primarily associated with the cell-membrane fraction. These observations are in general agreement with those of other investigators who have used the Caco-2 cell line in their studies (Hauri et al, 1985;Rousset et al, 1986;Steiger et al, 1988;Matter et al, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…At the present time, the reasons for this are unknown; however, similar studies with alkaline phosphatase reveal no differences in processing time for this particular enzyme (Matsumoto et al, 1990). Conversely, other studies have shown that there are differences in the processing time for different brush-border-membrane hydrolases, with the peptidases being processed at a faster rate than the disaccharidases in differentiated Caco-2 cells (Rousset et al, 1986;Steiger et al, 1988).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, a subapical cell compartment seems to function as a docking platform for vesicles containing functional proteins (98). Parental Caco-2 cells and clones have also been used to identify the mechanisms underlying the sorting and surface delivery of apical and basolateral proteins in human enterocytes (99)(100)(101)(102)(103)(104)(105)(106)(107) and to find out how functional intestinal proteins take their place in cell membrane domains, including brush border-associated functional proteins such as SI (82,84,86,90,94,100,106,(108)(109)(110)(111)(112)(113)(114), AP (110,111), lactasephlorizin hydrolase (108,115), maltase-glucoamylase (108), APN (90,108,111), DPP IV (82,90,100,108,(116)(117)(118)(119)(120)(121), angiotensin I-converting enzyme (108), ␣-glucosidase (122), p-aminobenzoic acid peptide hydrolase (108), SGLT1, GLUT1, GLUT2, GLUT3, and GLUT5 (123)(124)…”
Section: Differentiated Enterocyte-like Parental Caco-2 Cell Line Andmentioning
confidence: 99%
“…During 7 to 10 days in culture, these cells form polarized monolayers that have intercellular tight junctions and defined apical and basolateral surfaces. The differentiated apical surface has dense brush border microvilli containing normal intestinal brush border enzymes and antigens (13,18,43,44). A key advantage of differentiated Caco-2 cells is that they provide a substrate monolayer similar to that for which Campylobacter shows a natural tropism in vivo.…”
mentioning
confidence: 99%